The value of sorghum grain, corn and wheat fed individually and in varying combinations in beef cattle finishing rations - Richardson, D.; Smith, E.F.; Brent, B.E.; Clary, F.G. (Kansas Agricultural Experiment Station, 2011)
Sorghum grain is the predominant grain produced in Kansas for livestock. In general, sorghum grain may be expected to produce a rate of gain similar to corn and greater than wheat when fed to beef cattle. However, it is not normally as efficient from the standpoint of pounds required per pound of gain. Two feedlot trials have been conducted to determine the value of feeding mixtures of sorghum grain and corn or wheat.
Keywords: Beef; Sorghum grain; Corn; Wheat; Finishing rations